2021
DOI: 10.5194/wcd-2-507-2021
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional life cycles of potential vorticity cutoffs: a global and selected regional climatologies in ERA-Interim (1979–2018)

Abstract: Abstract. The aim of this study is to explore the nature of potential vorticity (PV) cutoff life cycles. While climatological frequencies of such near-tropopause cyclonic vortices are well known, their life cycle and in particular their three-dimensional evolution is poorly understood. To address this gap, a novel method is introduced that uses isentropic air parcel trajectories to track PV cutoffs as three-dimensional objects. With this method, we can distinguish the two fundamentally different PV cutoff lysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 85 publications
2
36
0
Order By: Relevance
“…The tracking algorithm extends the methodology by Wernli and Sprenger (2007), and makes use of 2d Lagrangian trajectory calculations based on the Chemical Lagrangian Model of the Stratosphere CLaMS (McKenna et al, 2002). A similar algorithm was recently developed by Portmann et al (2021). The principal idea is to initialize air parcels within the detected cutoffs at time t 0 , carry out a forward calculation of their trajectories over the time step ∆t, and subsequently compare the new positions with the detected cutoffs at time t 1 = t 0 + ∆t.…”
Section: Cutoff Detection and Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…The tracking algorithm extends the methodology by Wernli and Sprenger (2007), and makes use of 2d Lagrangian trajectory calculations based on the Chemical Lagrangian Model of the Stratosphere CLaMS (McKenna et al, 2002). A similar algorithm was recently developed by Portmann et al (2021). The principal idea is to initialize air parcels within the detected cutoffs at time t 0 , carry out a forward calculation of their trajectories over the time step ∆t, and subsequently compare the new positions with the detected cutoffs at time t 1 = t 0 + ∆t.…”
Section: Cutoff Detection and Trackingmentioning
confidence: 99%
“…tropospheric air of low PV in the stratosphere. An algorithm for tracking these cutoffs was recently developed by Portmann et al (2021). In this study, PV streamers and cutoffs are identified with reference to a chosen critical PV contour on an isentrope, representing the tropopause.…”
Section: Introductionmentioning
confidence: 99%
“…These elongated anomalies can have complex life cycles and behavior: They are often linked to Rossby wave breaking (RWB) events (e.g., McIntyre and Palmer, 1983;Thorncroft et al, 1993), interact with surface cyclones (e.g., Galarneau Jr et al, 2015;Bentley et al, 2017;Maier-Gerber et al, 2019), and may detach from the main stratospheric high-PV reservoir on a given isentropic level, forming so-called PV cutoffs. These cutoffs can diabatically decay, be reabsorbed by the main reservoir, undergo further dynamical processes, and can be associated with extreme weather events (Portmann et al, 2021).…”
mentioning
confidence: 99%
“…An identification of 3-D PV structures has previously been performed for subsets of anomalies only, although the importance of their vertical structure has been demonstrated in the literature (e.g. Portmann et al, 2021;Lamarque and Hess, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation